ENHANCEMENT OF GREEN BEAN PLANT (Vigna Radiata L.) HEIGHT GROWTH THROUGH SEED SOAKING IN COCONUT WATER: PENINGKATAN PERTUMBUHAN TINGGI TANAMAN KACANG HIJAU (Vigna Radiata L.) MELALUI PERENDAMAN BENIH DALAM AIR KELAPA - Halawa, Juliman (UPMI Proceeding Series, 2024)
This study aimed to investigate the effect of soaking mung bean seeds (Vigna Radiata L) in coconut water. A factorial Randomized Complete Block Design (RCBD) with 3 replications was used, with treatments: P0: control, P1: 2 hours, P2: 4 hours, P3: 6 hours. The parameter observed was plant height (cm). The results indicated that soaking mung bean seeds (Vigna Radiata L) in coconut water influenced plant growth, particularly in terms of plant height.